Biomarkers of vascular injury and type 2 Diabetes: a prospective study, systematic review and meta-analysis - Pletsch-Borba, Laura; Turzanski Fortner, Renée; Katzke, Verena; Johnson, Theron S.; Groß-Weissmann, Marie-Luise; Hoffmeister, Michael; Bugert, Peter; Kaaks, Rudolf; Kühn, Tilman (Journal of Clinical Medicine, 2019)
Data on biomarkers of vascular injury and type 2 diabetes (T2D) risk from prospective studies are lacking. We evaluated seven biomarkers of vascular injury in relation to T2D. Additionally, a meta-analysis was performed. From the EPIC–Heidelberg cohort, 2224 participants were followed-up from baseline for 16 (median) years. E-Selectin, P-Selectin, intercellular adhesion molecule 3 (ICAM3), thrombomodulin, thrombopoietin, glycoprotein IIb/IIIa and fibrinogen levels were measured in baseline blood samples. The systematic review and meta-analysis included prospective studies identified through MEDLINE and Web of Science that investigated the association between mentioned biomarkers and T2D. The study population included 55% women, median age was 50 years, and 163 developed T2D. ICAM3 was associated with lower T2D risk (fully adjusted HRhighest vs. lowest tertile 0.62 (95% CI: 0.43, 0.91)), but no other studies on ICAM3 were identified. Overall, fifteen studies were included in the systematic review and meta-analysis (6,171 cases). E-Selectin was associated with higher T2D risk HRper SD: 1.34 (95% CI: 1.16, 1.54; I2 = 63%, n = 9 studies), while thrombomodulin was associated with lower risk HRper SD: 0.82 (95% CI: 0.71, 0.95; I2 = 0%, n = 2 studies). In the EPIC–Heidelberg, ICAM3 was associated with lower T2D risk. The meta-analysis showed a consistent positive association between E-Selectin and T2D. It was also suggestive of an inverse association between thrombomodulin and T2D, although further studies are needed to corroborate this finding.